2022
DOI: 10.2147/idr.s363652
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Antibiotic Resistance, Biofilm Formation, and Biofilm-Specific Resistance in Escherichia coli Isolates from Ningbo, China

Abstract: Purpose Several Escherichia coli pathotypes still constitute an important public health concern owing to its pathogenicity and antimicrobial resistance. Moreover, biofilm formation of E. coli can allow the strains to interfere with host and antimicrobial eradication, thus conferring additional resistance. The association between the formation of biofilm and antimicrobial resistance determinants has been extensively exploited; nevertheless, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The results of this study showed the number of drug resistance of biofilm-positive strains was higher than that of biofilm-negative strains, further proving that the biofilmforming ability of bacteria is closely related to drug resistance. Similarly, Qian et al (2022) revealing that the populations that exhibited more robust biofilm formation…”
Section: Correlation Analysis Of Biofilm Formation Ability and Drug R...mentioning
confidence: 96%
“…The results of this study showed the number of drug resistance of biofilm-positive strains was higher than that of biofilm-negative strains, further proving that the biofilmforming ability of bacteria is closely related to drug resistance. Similarly, Qian et al (2022) revealing that the populations that exhibited more robust biofilm formation…”
Section: Correlation Analysis Of Biofilm Formation Ability and Drug R...mentioning
confidence: 96%
“…Additionally, the results revealed that non-susceptible isolates exhibited higher levels of biofilm formation compared to susceptible isolates in six categories, namely quinolones, fluoroquinolones, cephalosporins, aminoglycosides, macrolides, tetracyclines, and nitrofurans. The formation of biofilm was found to be similar in E. coli strains that were susceptible and those that were not susceptible to β -lactams and lipopeptides ( Qian et al., 2022 ). A systematic review and meta-analysis found that UPEC isolates that cause UTI frequently develop biofilms.…”
Section: E Coli Biofilms and Antibiotic Resistancementioning
confidence: 99%
“…43 According to Qian et al , there is a strong association between biofilm-forming ability in E. coli clinical isolates and resistance to cephalosporins such as ceftriaxone, cefoxitin, and cefazolin. 44 Similarly, Al-Bayati and Samarasinghe investigated that biofilm formation was related to carbapenem resistance. 43 The luxS gene was also highly expressed by E. coli and K. pneumonia throughout the biofilm formation process, demonstrating the importance of the QS system in biofilm formation.…”
Section: Resistance Of Enterobacteriaceaementioning
confidence: 99%